Masculinity : Male Traits in 1930s Portrayed in Public Enemies - Pita Merdeka; Kusumo Asri Kumoro (Insaniyat : Journal of Islam and Humanities, 2018)
This article discusses the masculinity of John Dillinger as the main male character inPublic Enemies Film (2009); directed by Michael Mann, and produced by Universal Pictures. This film is clearly described that men who appear strong, physically attractive, charming, and smart fall into the category of masculine.This study used descriptive qualitative method by using Janet Saltzman Chafetz’s concept of masculinity in seven areas or forms such as the physical image, the function in life, the sexual aggressiveness, the emotion, the intelligence, the personality, and other personality characteristics. In the first part of analysis, the research reveals the characteristics of John Dillinger utilizing Edward Jones’ Characterization theory, before assigning them to the seven areas or forms of Chafetz’s concept of masculinity.The result shows that the main male character,John Dillinger adjusts his characteristics based on the person he interacts with.John Dillinger as the main male character in Public Enemies film defines his position as a man in the society in the 1930s. He plays andtakes a dominant role as a leader for his gang members; his lover, Billie Frechette,by caring, protecting, and supporting them. On the other side, Dillinger is apathetic against the authority. He also takes pride in his reputation, and believes that he can achieve ambitions to be on top of the world.DOI: 10.15408/insaniyat.v2i2.7814